2022
DOI: 10.1002/smll.202107559
|View full text |Cite
|
Sign up to set email alerts
|

Biocoating—A Critical Step Governing the Oral Delivery of Polymeric Nanoparticles

Abstract: Decades of research into the topic of oral nanoparticle (NP) delivery has still not provided a clear consensus regarding which properties produce an effective oral drug delivery system. The surface properties—charge and bioadhesiveness—as well as in vitro and in vivo correlation seem to generate the greatest number of disagreements within the field. Herein, a mechanism underlying the in vivo behavior of NPs is proposed, which bridges the gaps between these disagreements. The mechanism relies on the idea of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
(220 reference statements)
0
4
0
Order By: Relevance
“…Previously, it was shown that negative surface charge correlates with mucoadhesiveness by forming hydrogen bonds with mucins [ 25 ]. Another study showed mucins can attach to negatively charged molecules via positively charged amino acids in the terminal domains [ 26 ]. Yet, it was also demonstrated that loose mucins in the lumen adhere to and coat charged NPs and may neutralize their effective surface charge [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that negative surface charge correlates with mucoadhesiveness by forming hydrogen bonds with mucins [ 25 ]. Another study showed mucins can attach to negatively charged molecules via positively charged amino acids in the terminal domains [ 26 ]. Yet, it was also demonstrated that loose mucins in the lumen adhere to and coat charged NPs and may neutralize their effective surface charge [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanodrug delivery platforms can transport malabsorbed drugs to the gastrointestinal tract and improve oral bioavailability. Coating nanoparticles with biological mucus modify their surface properties and increases the mucosal diffusion rate, gastrointestinal retention time, and systemic absorption ( Azagury et al, 2022 ). Modifying ligands on the surface of nanoparticles can also specifically target the gastrointestinal tract.…”
Section: Extravascular Targeting Nanoparticlesmentioning
confidence: 99%
“…In addition, to determine the potential stability of the obtained lipid nanoparticles, the zeta potential (ZP) was also measured. ZP is one of the key parameters describing the process of particle behavior in suspension and is used to analyze the electrostatic properties of suspensions [34]. It is assumed that the tested material can be considered stable if the absolute value of the zeta potential is greater than −30 mV [35,36].…”
Section: Optimization Of the Synthesis Of Solid Lipid Nanoparticlesmentioning
confidence: 99%